2020
DOI: 10.1371/journal.pone.0242261
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making on maternal pertussis vaccination among women in a vaccine-hesitant religious group: Stages and needs

Abstract: Introduction As of December 2019, pregnant women in the Netherlands are offered pertussis vaccination to protect their newborn infant against pertussis infection. However, the manner in which pregnant women decide about this maternal pertussis vaccination is largely unknown. The aim of this study is to gain insight into the decision-making process regarding maternal pertussis vaccination, and to explore the related needs among the vaccine-hesitant subgroup of orthodox Protestant women. Methods Charmaz’s grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 59 publications
2
17
0
Order By: Relevance
“…Our findings add to this body of literature by revealing informational (the feeling of being overwhelmed by the information regarding the COVID-19 vaccination), relational (the depersonalization of both the vaccinator and the vaccinated), moral (the particularly strong moral significance attached to the COVID-19 vaccination decision), and emotional (the fear of discrimination as a result of the vaccination decision) constraints to the COVID-19 vaccination decision-making process. First, while there is evidence that the vaccination decision-making process is shaped by one's information seeking behavior ( de Munter et al, 2020 ), our results indicate that excessive information constitutes a challenge to the decision. This finding is not surprising.…”
Section: Discussionmentioning
confidence: 64%
“…Our findings add to this body of literature by revealing informational (the feeling of being overwhelmed by the information regarding the COVID-19 vaccination), relational (the depersonalization of both the vaccinator and the vaccinated), moral (the particularly strong moral significance attached to the COVID-19 vaccination decision), and emotional (the fear of discrimination as a result of the vaccination decision) constraints to the COVID-19 vaccination decision-making process. First, while there is evidence that the vaccination decision-making process is shaped by one's information seeking behavior ( de Munter et al, 2020 ), our results indicate that excessive information constitutes a challenge to the decision. This finding is not surprising.…”
Section: Discussionmentioning
confidence: 64%
“…The second driver is also likely to apply to orthodox Protestants, although it is likely that rubella is a less discussed topic among friends and family members since the last outbreak occurred more than 15 years ago. Moreover, in line with the third driver, orthodox Protestant women's negative attitude can be partially explained by their indecisiveness or negative intention towards vaccination based on both religious and health-related aspects [18,19], supplemented by their perception that they had been infected with rubella as a child.…”
Section: Discussionmentioning
confidence: 97%
“…In a previously conducted study on maternal pertussis vaccination, orthodox Protestant women reported gathering information as an essential need to make a well-considered vaccination decision [18]. In addition to receiving information, women in the maternal pertussis vaccination study wanted sufficient time to search for information themselves, to converse with others about the vaccination, and to deliberate the values they consider to be important concerning the vaccination [18]. It can be assumed that unvaccinated women, when offered rubella screening or vaccination, also need both information and sufficient time to come to a deliberate, informed decision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain racial and ethnic groups, including Hispanic/Latinx and African American populations, have disproportionately higher prevalence of vaccine hesitancy (Kessels et al, 2012;Rutten et al, 2021). Similarly, social and religious beliefs, values, or norms can directly lower the rate of vaccination among tight-knit communities (de Munter et al, 2020;Ferrer et al, 2014;Joshi, Chaudhari, and Chaudhari, 2020;WHO, 2021). For instance, some conservative religious groups have endorsed beliefs that vaccination against human papillomavirus (HPV) leads to increased engagement in sexual activity (Fisher et al, 2013).…”
Section: Root Causes Of Vaccine Hesitancymentioning
confidence: 99%